Active K-OMS-2 supported catalyst for hydrogenolysis of glycerol - Gogoi, Pranjal; Chilukuri, Satyanarayana; Thirumalaiswamy, Raja (ChemistrySelect, 2021)
Propanediols are very important chemical intermediates, which need to be prepared through commercially viable routes. Cryptomelane type octahedral molecular sieve-2 (K-OMS-2), a cheap and environmentally benign microporous oxide was employed to support Ru and used as a catalyst to get 1,2-propanediol (1,2-PDO) selectively through hydrogenolysis of glycerol. Three catalysts with different Ru content were prepared and evaluated for glycerol hydrogenolysis. Among these, 1 wt.% Ru-K-OMS-2 showed reasonably good activity towards 1,2-PDO formation under moderate reaction conditions even at lower Ru loading (0.9 wt.%). When other metals such as Cu and Ni were supported on K-OMS-2, their performance was inferior compared to Ru-supported catalysts. All the catalysts were characterized using various physicochemical techniques like XRD, N-2-sorption, TPD, H-2-TPR, TGA, ICP-OES, FE-SEM and TEM. The enhanced catalytic activity with the 1 wt.%Ru-K-OMS-2 catalyst was attributed to the better Ru metal dispersion, higher active metal surface area, basic strength, and porosity of the support. The catalyst was found to be recyclable. Analysis of spent catalyst by TEM showed disintegration of Ru nanoparticles to smaller ones, under high H-2 pressure at the reaction temperature. Smaller Ru particles are expected to promote C-C bond cleavage thus suppressing 1,2-PDO formation. Furthermore, a relationship between the TOF value, Ru nanoparticles size, and the basic strength of the catalysts was established, which provides dipper insight into the different catalytic behavior of the catalysts.
Keywords: Glycerol; Hydrogenolysis; octahedral molecular sieves; Propanediols; selectivity